Complete genome of single locus sequence typing D1 strain Cutibacterium acnes CN6 isolated from healthy facial skin - Ikwhan Kim; Da-Ryung Jung; Ryeong-Hui Kim; Dokyung Lee; YeonGyun Jung; Ji Hoon Ha; Eun Kyung Lee; Jin Mo Kim; Jin Young Kim; Jun-Hwan Jang; Jun-Tae Bae; Yoon Soo Cho; et al. (BMC Genomic Data)
Abstract Objectives Cutibacterium acnes is a Gram-positive bacterium commonly found on human skin, particularly in sebaceous areas. While it is typically considered a commensal, specific strain types based on single locus sequence typing (SLST) have been associated with pathogenic conditions or healthy skin. Recently, SLST D1 strains, part of phylotype IA1, have received attention for their potential benefits related to skin health. However, their genetic characteristics remain underexplored. Therefore, the whole genome of C. acnes CN6, an SLST D1 strain isolated from the facial skin of a healthy individual, was sequenced to expand the understanding of SLST D1 strains and identify genomic features that may support skin health. Data description The whole genome sequencing of C. acnes CN6 was conducted using MinION reads based on de novo assembly, revealing a single circular complete chromosome. With the length of 2,550,458 bp and G + C content of 60.04%, the genome contains 2,492 genes, including 2,433 CDSs, 9 rRNAs, 46 tRNAs, 4 ncRNAs, and 134 pseudo genes. Previously predicted virulence proteins of C. ances were detected in the genome. Genome comparation with 200 C. acnes strains isolated from healthy facial skin revealed SLST D1 strain-specific genes and a unique variant of the znuC gene in D1 strains.